Prenatal diagnosis of 17q12 deletion syndrome: from fetal hyperechogenic kidneys to high risk for autism. (25th October 2016) - Gilboa, Yinon; Perlman, Sharon; Pode‐Shakked, Naomi; Pode‐Shakked, Ben; Shrim, Alon; Azaria‐Lahav, Einat; Dekel, Benjamin; Yonath, Hagith; Berkenstadt, Michal; Achiron, Reuven
Abstract: Objective: The linkage between 17q12 microdeletions, renal anomalies, and higher risk for neurodevelopmental disorders is well described in the literature. The current study presents prenatal diagnosis of normal‐sized fetal hyperechogenic kidneys leading to the diagnosis of 17q12 deletion syndrome and autism spectrum disorder. Methods: Over a period of 9 years in a single referral center, seven fetuses were diagnosed with hyperechogenic renal parenchyma and were followed up prospectively. Amniocentesis for molecular diagnosis was performed in all cases, and subsequently, five fetuses were found to harbor a 17q12 deletion by chromosomal microarray analysis. Postnatal evaluation was carried out by a developmental neurologist. Results: Five of the seven fetuses had molecular diagnosis of 17q12 deletion. One patient elected termination of pregnancy. On long‐term follow‐up, all of the four children showed symptoms consistent with neurodevelopmental disorders. The two fetuses with no deletion have a normal follow‐up with regression of the renal hyperechogenicity. Conclusions: We report a strikingly high correlation between prenatal hyperechogenic kidneys, 17q12 microdeletion, and autism spectrum disorder with the advantage of optimal prenatal counseling as well as early diagnosis and intervention. © 2016 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? Microdeletions involving 17q12 were described with solid evidence to be associated with renal abnormalities as well as neurodevelopmental disorders in children and adults. Pre‐symptomatic diagnosis of high‐risk cases for neurodevelopmental delay has paramount advantage in identifying as early as possible those who would benefit from close assessment and psychological intervention. What does this study add? Prenatal diagnosis of 17q12 deletion syndrome following diagnosis of normal‐sized fetal echogenic kidneys may allow earlier diagnosis and intervention in cases of autistic spectrum and neurodevelopmental disorders.